First Case Report of Bilateral Spontaneous Otogenic Pneumocephalus - Voldřich, Richard; Májovský, Martin; Chovanec, Martin; Netuka, David (World neurosurgery, 2019)
BACKGROUND: Pneumocephalus is commonly associated with cranial trauma including surgical interventions. Spontaneous pneumocephalus on the other hand is a rare diagnosis. Reported cases were predominantly unilateral. We report a unique case of a bilateral spontaneous pneumocephalus probably related to a bilateral tegmen defect related to repeated Politzer maneuvers. CASE DESCRIPTION: A 78-year-old man suffered from vertigo, tinnitus, instability, and mild expressive aphasia. In the past 12 weeks before clinical deterioration he underwent series of Politzer maneuvers performed for repetitive inflammation of upper respiratory tract with otitis media. Brain computed tomography revealed a large bilateral collection of intracranial air with associated tegmen defects. Primarily, surgical revision of the middle fossa and multilayer reconstruction of the dura and skull base defect on the left side was performed. After 5 days, the other side was reconstructed in a similar way. Postoperative course was uneventful with brisk improvement of symptomatology. Both computed tomography scans undertaken after the first and second surgery showed satisfying regression of intracranial air. CONCLUSIONS: Spontaneous pneumocephalus represents a rare condition often associated with increased middle ear pressure, which can be caused by autoinflation (e.g., Valsalva or Politzer maneuver), sneezing, or coughing. The described case represents a unique presentation of the bilateral spontaneous pneumocephalus associated with bilateral tegmen and dura mater defects managed surgically. Despite its rarity, spontaneous pneumocephalus originating from the temporal bone should be considered as a possible diagnosis in patients with suggestive otologic presentation (e.g., tinnitus, instability, hearing loss) and associated nonspecific neurologic symptomatology.
Keywords: senioři; pneumocefalus; Tegmen defects; Skull Base; mužské pohlaví; Temporal encephalocele; Humans; baze lební; spánková kost; Temporal Bone; Aged; Spontaneous pneumocephalus; Superior semicircular canal dehiscence; Complication; Pneumocephalus; lidé; Male; Politzer maneuever